Early results of a high friction surface coated uncemented socket in revision hip arthroplasty. Issue 6 (November 2020) - Chacko, Vinay; Agrawal, Pranshu; Porter, Martyn L; Board, Tim N
Background: Revision hip arthroplasty with high friction trabecular metal sockets has resulted in good medium-term results. Many manufacturers have therefore introduced higher friction coatings to their implants to meet a growing demand for similar implants. The Pinnacle Gription was introduced in 2007 as an evolution of the standard Pinnacle socket. This study aimed to assess the early results of this socket in a revision setting. Methods: Between August 2009 and December 2016, the Gription socket was used in 146 revision hip replacements. The mean age was 63 (19–88) years. Defects were classified as Paprosky Grade 2 in 71(2A [28], 2B [19], 2C [24]) and grade 3 in 20 (3A [18], 3B [2]). Bearing combinations were ceramic-on-ceramic in 23, metal-on-polyethylene in 71, ceramic-on-polyethylene in 52. Screws were used in 112 cases, impaction bone grafting in 34 and metal augments in 1 case. Radiographs were analysed for progressive radiolucent lines and migration. Results: Mean follow-up was 43.5 (range 25–62) months. There were 6 re-revisions (2 for deep infection, 2 for recurrent dislocation and 2 for aseptic loosening). None of the other cases had evidence of socket migration or progressive radiolucent lines. There were no intraoperative or postoperative periprosthetic fractures. The crude survivorship for all-cause failure was 95.8% and the survivorship for aseptic loosening was 98.6%. at 43.5 months follow-up. Conclusions: This is the largest reported series of Gription socket use in revision arthroplasty and demonstrates encouraging early results. We therefore advocate the continued cautious use of this implant.